Pathogenesis of bacterial infections in animals - Prescott, John F. (John Francis) 1949-; MacInnes, Janet I.; van Immerseel, Filip; Boyce, John; Rycroft, Andrew N. 1955-; Vazquez-Boland, Jose A. (Hoboken, New Jersey Wiley-Blackwell, 2023)
"Pathogenesis of Bacterial Infections in Animals, Fifth Edition is a specialist reference that provides a comprehensive review of bacterial pathogens in animals and their interplay with complex disease processes, offering a complete understanding of how bacteria cause disease and covering recent advances in the field and new taxonomies. In the newly revised fifth edition, additional introductory chapters have been added to help to set the material in context, and more figures have also been added to improve understanding and comprehension throughout the text. A companion website presents the figures from the book in PowerPoint and references. This detailed reference includes novel approaches to controlling bacterial pathogens in light of growing concerns about antimicrobial resistance, with more than 70 expert authors sharing their wisdom on the topic. While molecular pathogenesis is a major aspect in almost every chapter, the authors have been careful to place pathogens in their broader context. Pathogenesis of Bacterial Infections in Animals, Fifth Edition is an essential resource for graduate students in veterinary medicine and animal science, microbiologists, virologists, and pathologists. It is the only book to cover this topic to this depth through the insight of dozens of qualified and practicing professionals"--
Chapter 1: Themes in Bacterial Pathogenesis; Chapter 2: Evolution of Bacterial Pathogens; Chapter 3: Understanding Pathogenesis Through Pathogenomics and Bioinformatics; Chapter 4: Experimental Approaches to Understanding Pathogenesis; Chapter 5: Subversion of the Immune Response by Bacterial Pathogens; Chapter 6: Chinks in the Armor: Pathogenesis-Based Strategies to Combat Bacterial Infections; Chapter 7: Escherichia coli; Chapter 8: Salmonella; Chapter 9: Yersinia; Chapter 10: Pasteurella; Chapter 11: Mannheimia and Bibersteinia; Chapter 12: Actinobacillus; Chapter 13: Other Pasteurellaceae: Avibacterium, Bibersteinia, Gallibacterium, Glaesserella, and Histophilus; Chapter 14: Pseudomonas; Chapter 15: Moraxella; Chapter 16: Brucella; Chapter 17: Bordetella; Chapter 18: Campylobacter; Chapter 19: Helicobacter; Chapter 20: Chlamydia and Coxiella; Chapter 21: Rickettsiales; Chapter 22: Lawsonia intracellularis; Chapter 23: Leptospira; Chapter 24: Brachyspira; Chapter 25: Staphylococcus; Chapter 26: Streptococcus; Chapter 27: Bacillus anthracis; Chapter 28: Enteric Clostridia; Chapter 29: Histotoxic Clostridia; Chapter 30: Neurotoxic Clostridia; Chapter 31: Mycoplasmas; Chapter 32: Corynebacterium, Arcanobacterium, and Trueperella; Chapter 33: Rhodococcus equi; Chapter 34: Mycobacterium; Chapter 35: Gram-Negative Anaerobes; Index
UP System perpetual contents
Includes bibliographical references and index
Keywords: Bacterial diseases in animals; Veterinary bacteriology; Pathogenic microorganisms